Psychological assistance to patients with near-death experience (based on foreign research) - Olga V. Gordeeva (Национальный психологический журнал, 2018)
Background. Near-death experience is an altered state of consciousness at the time when the person is on the threshold of death. Near-death experience has a specific structure which includes such elements as extra corporal experience, moving in a dark tunnel, seeing bright light, meetings with the deceased persons, panoramic life review and many others. The condition is quite common nowadays particularly due to the success of resuscitation and a high level of emergency care organization). Experience in itself and its some consequences derivate a lot of psychological problems at the person, which he is afraid to tell not only medical staff, but also relatives because of danger of interpretation his (her) near-death experiences as marks of psychic illness. The Objective of the analytical theoretical research was to study the experience of working with such patients, accumulated in Western medicine, psychology and psychotherapy, the organization of the training process and also the organization of psychotherapeutic support for survivors and members of their families. Design. This article analyzes the foreign (most publications on this subject is carried out in the United States) works on the problem of treatment with near-death experiencer and psychological support for them, the material contained in these works is structured and summarized on the main problems in this area. Research results. Based on the review and analysis of the reference literature a preliminary Atwater’s adaptation model of the near-death experience is proposed, the integration of this experience is viewed as the main goal to be implemented by the experiencer independently or in collaboration with a psychotherapist, the universal rules of treating near-death experiencers are elaborated. There are rules of treating different groups of experiencers and different categories of people interacting with them are identified and integrated: the rules of treating children with near-death, the experience of organizing psychotherapeutic assistance to their relatives. Conclusion. The compliance with the rules by physicians, psychotherapists and relatives of near-death patients contributes to the decreased emotional and social problems in the patient, and sometimes even prevents their occurrence.